2018
DOI: 10.1016/s1470-2045(18)30144-x
|View full text |Cite
|
Sign up to set email alerts
|

Durvalumab as third-line or later treatment for advanced non-small-cell lung cancer (ATLANTIC): an open-label, single-arm, phase 2 study

Abstract: AstraZeneca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
381
4
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 485 publications
(418 citation statements)
references
References 27 publications
25
381
4
1
Order By: Relevance
“…22 Most recently, in the Supplementary data of a large scale phase 2 study (ATLANTIC) that included 15 ALK-positive NSCLC patients treated with durvalumab as third-line or later therapy, ALK-positive NSCLC patients had a tendency of poor OS and PFS compared to EGFR-positive patients. 23 These findings are consistent with our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…22 Most recently, in the Supplementary data of a large scale phase 2 study (ATLANTIC) that included 15 ALK-positive NSCLC patients treated with durvalumab as third-line or later therapy, ALK-positive NSCLC patients had a tendency of poor OS and PFS compared to EGFR-positive patients. 23 These findings are consistent with our study.…”
Section: Discussionsupporting
confidence: 93%
“…A retrospective study including six ALK‐positive NSCLC patients found ALK rearrangement to be associated with low overall response rates to PD‐1/PD‐L1 blockade . Most recently, in the Supplementary data of a large scale phase 2 study (ATLANTIC) that included 15 ALK‐positive NSCLC patients treated with durvalumab as third‐line or later therapy, ALK‐positive NSCLC patients had a tendency of poor OS and PFS compared to EGFR‐positive patients . These findings are consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Median sPD-L1 titer was below the LLOQ at the end of infusion on day 1 of dose 1 and again at the end of treatment for all dose groups. At 3 months after the end of treatment, one of one evaluable patient in the 1.0 mg/kg q2w dose group and one of two evaluable patients in the 20 mg/kg q4w dose group had a detectable sPD-L1 titer, with titers of 82.3 and 142, respectively.4 | D ISCUSS I ONOverall, durvalumab was generally well tolerated without DLT in these patients with a range of solid tumor types, including gastric/ gastroesophageal cancer, NSCLC, and other advanced solid tumors.Number of patients with trAE was similar across the dose groups, and consistent with previous reports of PD-1/PD-L1 blockade in general[17][18][19][20][21] and durvalumab specifically;13,15,22,23 the most frequently occurring trAE in accordance with their immune-mediated mechanism were rash and pruritus. Few treatment-related grade ≥3 events occurred in any of the dosing groups.…”
supporting
confidence: 89%
“…These results suggested the efficacy of atezolizumab in the third‐line treatment for patients with advanced NSCLC. In another phase II trial (ATLANTIC), the ORR of durvalumab in patients with NSCLC with EGFR and ALK positivity and ≥25% of tumor cells expressing PD‐L1 was 12.2%, which was lower than those with EGFR and ALK negativity (16.4%) or those with ≥90% PD‐L1 expression of tumor cells (30.9%) . Because the clinical trials in this stage are limited, the efficacy of PD‐1/PD‐L1 blockade therapy might be warranted with more phase III trials.…”
Section: Pd‐1/pd‐l1 Blockade Therapy In Advanced Nsclcmentioning
confidence: 99%